2018
DOI: 10.1016/j.mran.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The use of quantitative microbial risk assessment to estimate the health risk from viral water exposures in sub-Saharan Africa: A review

Abstract: Access to microbiologically safe water is not a reality for many people throughout Sub-Saharan Africa where there is widespread occurrence of viruses in water sources. Exposure to this water can lead to adverse health risks including diarrhoeal disease. To a limited extent in Sub-Saharan Africa, the quantification of the human health risk associated with exposure to virally contaminated water has been done through the use of quantitative microbial risk assessment (QMRA). To understand the scope of the informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…In this study, the harmonization factor (to convert qPCR results to dose–response model inputs) was varied uniformly from 0 to 1 for C. jejuni and Shigella and from 1.43 × 10 –3 to 0.1 for adenovirus due to the variable assumptions used in the existing literature. , Sensitivity analysis results were consistent with other QMRA studies performed in resource-limited settings showing model sensitivity to concentration data, , exposure parameters, ,, and dose–response parameters. , …”
Section: Resultssupporting
confidence: 70%
“…In this study, the harmonization factor (to convert qPCR results to dose–response model inputs) was varied uniformly from 0 to 1 for C. jejuni and Shigella and from 1.43 × 10 –3 to 0.1 for adenovirus due to the variable assumptions used in the existing literature. , Sensitivity analysis results were consistent with other QMRA studies performed in resource-limited settings showing model sensitivity to concentration data, , exposure parameters, ,, and dose–response parameters. , …”
Section: Resultssupporting
confidence: 70%
“…Additionally, Quantitative Microbial Risk Assessment (QMRA) could be used to estimate population health risks posed by these waterborne pathogens and inform water management strategies (Howard et al 2006;Owens et al 2020). Although QMRA has been widely used in developed countries (Bichai and Smeets 2013;Owens et al 2020), less-developed countries such as those in Africa, with limited data and resources, have greater challenges when applying this technique (Howard et al 2006;Chigor et al 2014;Van Abel and Taylor 2018). A recent review of QMRA in sub-Saharan Africa (Van Abel and Taylor 2018) outlined these challenges such as the lack of quantification data and defined several steps including the collection of further data on virus detection, concentration and infectivity, to improve this methodology within the region.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Atangana 2021 found that groundwater in South Africa contains heavy metals [65]. Van Abel 2018 stated that in South Africa, the frequency of virus exposure (with a range of 10−4-1011 viruses/L) from water, especially drinking, ground, irrigation, surface, and waste waters, is extremely high [66]. Adverse health risks, including those from NTDs, are associated with these water risks.…”
Section: Health and Watermentioning
confidence: 99%